Targeting interleukin-10 signalling for cancer immunotherapy, a promising and complicated task. Issue 10 (2nd October 2020) - Ni, Guoying; Zhang, Lu; Yang, Xiaodan; Li, Hejie; Ma, Bowei; Walton, Shelley; Wu, Xiaolian; Yuan, Jianwei; Wang, Tianfang; Liu, Xiaosong
ABSTRACT: Interleukin 10 (IL-10) belongs to IL-10 family cytokines that are critical for maintaining the integrity of epithelial tissues, protecting pathogenic infection, and preventing excessive immune responses to damage self. Temporal IL-10 signaling blockade enhances vaccine-induced tumor regression by CD8 + T cells. IL-10, especially pegylated IL-10, mediates tumor regression by expanding tumor-infiltrating CD8 + T cells. Moreover, targeting IL-10 enhances immune checkpoint inhibitor mediated tumor regression. In the current paper, we will review recent advances in this area and discuss the complexity of IL-10 manipulation for cancer therapy.